The Effect of Slice Thickness Variation on The Anatomical Information of CT Scan Paranasal Sinus Coronal Section in Clinical Rhinosinusitis - Luh Gede Yunda Rustika Putri; I Putu Eka Juliantara; I Made Purwa Darmita (Jurnal EduHealth, 2023)
CT Scan is an excellent technique in assessing anatomical structures, anatomical abnormalities, and visualising the presence or absence of pathological tissue in the four sinuses and their extensions. One of the important parameters on CT Scan is slice thickness. Slice thickness is a thickness of the slice that can be adjusted according to clinical requirements with a variation of values from 1 to 10 mm. The purpose of this study is to determine the effect of slice thickness variation on anatomical information of CT Scan paranasal sinus coronal section in rhinosinusitis and slice thickness variation that produces the most optimal anatomical information. This study is an analytical quantitative study with an experimental approach conducted on 10 samples who performed CT scan examination of paranasal sinus in rhinosinusitis using slice thickness variations of 0.6 mm, 1 mm, 1.5 mm and 2 mm. Based on the results of Friedman test and Wilcoxon Post Hoc test, the p value is 0.0001 (p<0.05) which means there is an effect of using slice thickness variation on anatomical information. The mean rank value in the Friedman test for slice thickness variations of 0.6 mm is 3.70, 1 mm is 3.13, 1.5 mm is 1.85, and 2 mm is 1.32 so based on the test results, slice thickness variation that shows the most optimal anatomical information is 0.6 mm.